The Development of Project Based Learning Model Based on Local Wisdom - Tri Kuat; Budi Santosa; I Ketut Yudiana; A. Shah (Graduate School of Universitas Negeri Malang, 2022)
Abstract: This study aimed to analyze the implementation of Project Based Learning (PjBL) on Creative Products and Entrepreneurship subject (PKK) in SMK, develop PjBL based on local wisdom in PKK subject, and analyze the effectiveness of developed PjBL in PKK. This research design was R&D. PjBL development used the ADDIE model. The research location is at SMK Bima Sakti Batanghari Nuban class XI TP totaling 29 students. Data were obtained through interview and questionnaires. The current PjBL result showed ineffectiveness to be applied. Then, the development of PjBL based on local wisdom showed the significant feasibility and effectiveness to be implemented.